(untitled) (Journal of Economic Research & Business Administration, 2018)
The concept of competitiveness is the central category of a market economy and, in general, determines the potential ability of various market actors to successfully compete with their competitors. However, the competitiveness of a commodity is characterized not only by its potential, but also by strategic opportunities for implementing, strengthening and expanding its market positions in the future. To date, Kazakhstan demonstrates a large increase in exports of extractive industries. However, the share of processed products with high added value in the country’s export structure remains low. It is necessary to increase the presence of science-intensive, innovative products in various industries and agriculture in the context of growing international competition in the export portfolio of Kazakhstan. To achieve this goal, a system of measures is required to increase the science intensity of GDP, the program for training scientific and professional personnel, create an innovation infrastructure and support innovative activities, as well as conditions for an international transfer of technology, creating favorable conditions for attracting foreign investment in the high-tech sector of the economy. In the article the authors examine the current situation on the foreign trade market of the RK for the last 3 years, where the group “Mineral Resources” is considered as the basis of analysis, the main share of which constitutes up to 70% of all raw materials extracted by the mining industries. The world market, where prices have been falling for the last three years and the export component of the RK has fallen by 60% compared to 2014, forces the Kazakh governance to change the structure of the economy towards diversification and industrialization of mining enterprises.